Are the perceptual-motor skills of 7–8-year-old girls able to predict the socio-economic status of the family? - Narges Zalnejad; Seyed Hojjat Zamani Sani; Mohammad Taghi Aghdasi (مطالعات عملکردی در روانشناسی ورزشی)
The socioeconomic status of the family is one of the most important environmental factors that affects the fetus, newborn, and child at different periods. Accordingly, the aim of the present study was to investigate the ability to predict the socioeconomic status of the family from various perceptual-motor skills of 7-8-year-old girls. In this retrospective study, 113 7-8-year-old girls were examined in two groups with appropriate (55 people) and inappropriate (58 people) socioeconomic status. The socioeconomic status assessment questionnaire, Stay in Step screening test, part of the Broninek-Ozeretsky test, and visual search test were used. Data analysis was also performed with discriminant analysis at a significance level of 0.05 and SPSS 23 software. Statistical findings showed that there was a significant difference between the groups with good and bad socioeconomic status in gross motor skills (all variables), hand-foot and hand-eye coordination, fine motor skills (only coins), and perceptual-motor skills only in items that measured mainly more difficult skills (with a large number of confounders = 64). Gross motor skills and motor coordination in girls with bad socioeconomic status were 93% accurate, while fine motor skills and perceptual-motor skills in girls with good socioeconomic status were 71% and 76% accurate, respectively. Gross motor skills and hand-eye coordination and hand-foot coordination were better accurate for children with bad socioeconomic status.